Genome-Wide Analysis of the SWEET Transporters and Their Potential Role in Response to Cold Stress in Rosa rugosa - Ronghui Li; Peng Gao; Tao Yang; Jie Dong; Yunting Chen; Yangyang Xie; Yvtong Yang; Chengzhi Liu; Jinzhu Zhang; Daidi Che (Horticulturae, 2023)
Sugar Will Eventually be Exported Transporter (SWEET) proteins are a recently discovered group of efflux transporters that play essential roles in sugar efflux, phloem loading, reproductive tissue development and stress responses. To date, there have been no reports on the Rosa rugosa (R. rugosa) SWEET genes. In this study, we conducted a comprehensive genomic analysis of the SWEET genes, including chromosome localization, phylogenetic comparison, cis-regulatory element analysis, expression pattern analysis in different tissues, expression pattern analysis under cold stress and subcellular localization analysis. A total of 33RrSWEET members were identified and classified into four distinct clades (Clade I, Clade II, Clade III and Clade IV). They were distributed across seven chromosomes and contained cis-regulatory elements associated with hormone and stress responses. The expression of RrSWEETs showed tissue specificity, with higher expression in roots, flowers or pistils compared to other tissues. Furthermore, during the entire cold stress process, the relative expression levels of RrSWEET4, 16 and 20 were significantly upregulated, especially in the roots and stems of R. rugosa. Subcellular localization analysis revealed that RrSWEET4, 16 and 20 were located on the cell membrane. In summary, the results of this study provide a theoretical basis for future research on the functions of RrSWEET genes in R. rugosa and their role in cold tolerance responses.